Congenital anomalies of the aortic arch - Priya, Sarv (Cardiovasc Diagn Ther, 2018)
Congenital anomalies of the aortic arch include diverse subgroups of malformations that may be clinically silent or may present with severe respiratory or esophageal symptoms especially when associated with complete vascular rings. These anomalies may be isolated or may be associated with other congenital heart diseases. Volume rendered computed tomography (CT) and magnetic resonance angiography (MRA) help in preoperative surgical planning by providing information about the complex relationship of aortic arch and its branches to the trachea and esophagus. Three dimensional capabilities of both computed tomography angiography (CTA) and MRA are helpful in determining evidence of tracheal or esophageal compression or other high-risk features in patients with a complete vascular ring.